SOCIO-ECONOMIC DETERMINANTS OF HEALTH-SEEKING BEHAVIOR AMONG THE YOUTH AGED 14-18 YEARS ATTENDING KASOZI HEALTH CENTRE III, WAKISO DISTRICT A CROSS-SECTIONAL STUDY. - Nabagereka , Harriet; Nalubuga, Bernadette (SJ Insights, 2025)
Background Globally, 311,000 people die in lower-income countries due to challenges with health-seeking behavior whereas 82% of the youths in Uganda do not seek health services even when they need to (Musoke et al., 2014). Statistics from Kasozi Health Center III show that many youths exhibit poor health-seeking behavior, which poses a risk for the youths hence living hazardous behaviors. This study therefore aims to identify the socio-economic determinants of health-seeking behavior among the youth aged 14-18 years attending Kasozi Health Centre III, Wakiso District. Methodology The study employed a descriptive and cross-sectional study using a quantitative method of data collection. A sample of 30 respondents was selected using a simple random sampling method. Data was collected using a questionnaire, analyzed, and presented in the form of tables, graphs, and pie charts. Results Results from the study revealed that the majority (60%) of the participants were females with (73%) being aged 16-18 years. The highest number (67%) of the participants were unemployed with (87%) of them earning between 100,000/= - 500,000/= per month which made it hard for them to access private facilities (60%) received medical services from the government and (53%) financial support from family members. Conclusion The highest number of the participants were unemployed earning between 100,000/= - 500,000/= per month with 6-10 family members. They received medical services from the government as well as financial support from family members. Recommendation Youths should often be encouraged to seek health care at the health facility and they should be given a conducive atmosphere to open up.